URGENSI PENERAPAN PRINSIP SYARIAH TERHADAP LEMBAGA KEUANGAN SYARIAH - Mayang Rosana (Lunggi Journal, 2023)
Sharia financial institute it birth the potency to grow and to birth a huge advantage for the Indonesian Economy. Observing the principles of Islamic sharia is an significant affair in the functions of sharia financial institute. Sharia financial institute is not only bank, but also Sharia financial institute nonbank. The standars of Shariah financial institute is differs from conventional financial institution. Financial Service Authority (OJK) as an institution the controller and the supervisor at the Sharia financial institute also have a fuction and authorization to do policy integration,strategy, and perfection stage at Sharia financial institute. Regulation instrument the issue should of course be in suitable with sharia principles by getting involved National Sharia Council (DSN) and Indonesian Council of Religious Scholar (MUI). Supervision of the application of sharia standars to sharia financial institute is imperative. The results of the application standars of the sharia fund will be the resolution of increasing public trust in sharia financial institute.